In Vitro Screening of Chinese Medicinal Plants for Antifungal Activity against Saprolegnia sp. and Achlya klebsiana. (1st August 2013) - Xue‐Gang, Hu; Lei, Liu; Cheng, Chi; Kun, Hu; Xian‐Le, Yang; Gao‐Xue, Wang
Abstract: Saprolegniasis is a common fungal disease in aquaculture, causing severe damage to cultured fishes. To find natural agents for controlling and treating saprolegniasis, we investigated methanol extracts of 40 traditional Chinese medicinal plants. Saprolegnia sp. strain JL and Achlya klebsiana were used to evaluate the antifungal activity of the plants. Cnidium monnieri, Magnolia officinalis, and Aucklandia lappa at a concentration of 62.5 mg/mL exhibited antifungal activity on Saprolegnia and Achlya klebsiana mycelium and were selected for further evaluation. The three plant species were extracted with four solvents (petroleum ether [PE], ethyl acetate, methanol, and water), and the extracts were evaluated with an in vitro bioassay using a rapeseed ( Brassica napus ) microplate method. Among the extracts tested, the PE extracts of the three plants exhibited the highest efficacy. The PE extract of A. lappa exhibited the best anti‐ Saprolegnia and anti‐ Achlya activities (50% effective concentrations = 11.3 and 26.1 mg/L, respectively), followed by C. monnieri and M. officinalis . Furthermore, the minimum fungicidal concentrations of PE extracts from the three herbs were identified as 25, 12.5, and 25 mg/L, respectively, against Saprolegnia spores and 25, 25, and 12.5 mg/L, respectively, against Achlya klebsiana spores. These findings demonstrate that the three traditional Chinese medicinal plants —A. lappa, C. monnieri, and M. officinalis —have the potential for use in developing a novel therapy to control saprolegniasis in aquaculture.